Necrotizing Enterocolitis in Full Term Neonates: Is There Always an Underlying Cause? - Olivier Abbo; Luke Harper; Jean-Luc Michel; Dushka Ramful; Audrey Breden; Frederique Sauvat (EL-Med-Pub, 2013)
Objective: To review our experience with full-term neonates with necrotizing enterocolitis (NEC) and to compare its characteristics to those published in the literature. Design: Retrospective review of all neonates born after 35 weeks of gestation managed in Reunion Island for NEC from 2000 to 2012. Results: Among the 217 diagnosed NEC, 27 patients (12.4%) were full term neonates, who were born at a mean gestational age of 36.8 ±1.7 weeks. The mean onset of the disease was 12.1±11.2 days after birth. Twenty patients had underlying causes (15 organic pathologies of the child, 3 isolated maternal disease, and 2 infections); 7 had idiopathic NEC. Surgery was required in 12 patients (37.5%) at 23.2±20 days after birth. NEC affected most of the time the colon (n=6) and the rectum (n=3). Overall survival rate was 88.8% (24/27). Two patients required partial non-enteral nutrition for1.3 and 2.1 years. Conclusions: NEC in full term neonates is a rare pathology. The onset of the disease in our experience was slightly later than described in the literature, but remains earlier than in the premature population. In some cases, no obvious cause can be found, suggesting a different pathogenesis. Further investigations are required in order to better understand this pathology. The goal will be to find measures to reduce global mortality.